2021
DOI: 10.3390/ani11030634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rearing Aviary Style and Genetic Strain on the Locomotion and Musculoskeletal Characteristics of Layer Pullets

Abstract: Previous research indicates that the musculoskeletal development of pullets is improved when pullets are reared in aviaries compared to conventional rearing cages. However, there are considerable differences in rearing aviary design. To measure locomotion and musculoskeletal development of brown (n = 7) and white-feathered (n = 8) strains of pullets, 15 commercial flocks in three styles of rearing aviaries differing in structural complexity (n = 5 per style) were visited three times: 25.9 ± 6.67, 68.0 ± 4.78, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…Ground-level feeders were used over elevated feeders in brown-feathered birds regardless of clipping treatment. This result expands on the general results of other studies where brown-feathered birds are less aerial than white-feathered birds [ 14 , 16 , 43 ]. Unexpectedly, there was no difference in half-clipped and fully clipped brown-feathered birds in their usage of the ground feeder.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Ground-level feeders were used over elevated feeders in brown-feathered birds regardless of clipping treatment. This result expands on the general results of other studies where brown-feathered birds are less aerial than white-feathered birds [ 14 , 16 , 43 ]. Unexpectedly, there was no difference in half-clipped and fully clipped brown-feathered birds in their usage of the ground feeder.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast with many flying species of birds, ground-dwelling species, such as chickens, will only fly infrequently, mainly to avoid predation and locate safe sleeping or roosting spaces [11][12][13]. Domestic birds kept for egg-laying (Gallus gallus domesticus) navigate their living space by walking, running, climbing, wing-assisted running and short-burst flapping flight [14][15][16]. Despite being ground birds, laying hens are highly motivated to roost using an elevated perch [17].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast to their white-feathered counterparts, brown-feathered caged birds only displayed a significant thickness increase of the supracoracoideus. Potentially, the ground-dwelling nature of brown-feathered birds [ 43 , 44 , 65 ] resulted in the minimal load-bearing activity of the wings prior to treatment, and the disuse of the wings did not differ enough to produce changes. Under partial immobilization, birds were still able to use one wing and walk around, which we hypothesized would reduce flight muscle (ipsilateral) but increase leg muscle thickness.…”
Section: Discussionmentioning
confidence: 99%
“…There are considerable differences in rearing aviary design. A recent study found that strain, as well as differences in rearing aviary design, can affect the types of locomotion that growing pullets perform, which may, in turn, impact their skeletal development [ 115 ]. Thus, it is recommended to raise pullets in a complex aviary system or a diverse environment during the early rearing period, regardless of the stereoscopic enrichment provided during the laying period [ 97 ].…”
Section: Effects Of Structural Equipmentmentioning
confidence: 99%